2011
DOI: 10.1289/ehp.1002470
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, Biochemical, and Environmental Factors Associated with Pregnancy Outcomes in Newborns from the Czech Republic

Abstract: BackgroundOxidative damage to placental DNA can result in negative pregnancy outcomes, including intrauterine growth restriction (IUGR) and low birth weight (LBW).ObjectiveWe investigated associations between the levels of 8-oxo-7,8-dihydro-2′-deoxyguanosine (8-oxodG), a marker of oxidative DNA damage, in placental DNA, exposure to air pollutants during pregnancy, genetic polymorphisms in 94 selected genes, and pregnancy outcomes.MethodsWe studied 891 newborns who were IUGR- or LBW-affected or normal weight an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Any disruption in the efficiency of transplacental function in utero has the potential to negatively impact fetal growth and development, particularly during critical periods of organogenesis (Stevenson et al, 2003). Epidemiologic evidence suggests an association between PM 10 and PM 2.5 exposure during pregnancy and adverse birth outcomes, including increased infant mortality, LBW, IUGR, and preterm birth (Bell et al, 2010b; Rossner et al, 2011; Rudra et al, 2011). Similar studies have demonstrated no association between fetal air pollution exposure and LBW, suggesting that the correlation between exposure and effect is delicate and might be enhanced by external factors such as region, SES, and duration of exposure (Rossner et al, 2011).…”
Section: Adverse Birth Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Any disruption in the efficiency of transplacental function in utero has the potential to negatively impact fetal growth and development, particularly during critical periods of organogenesis (Stevenson et al, 2003). Epidemiologic evidence suggests an association between PM 10 and PM 2.5 exposure during pregnancy and adverse birth outcomes, including increased infant mortality, LBW, IUGR, and preterm birth (Bell et al, 2010b; Rossner et al, 2011; Rudra et al, 2011). Similar studies have demonstrated no association between fetal air pollution exposure and LBW, suggesting that the correlation between exposure and effect is delicate and might be enhanced by external factors such as region, SES, and duration of exposure (Rossner et al, 2011).…”
Section: Adverse Birth Outcomesmentioning
confidence: 99%
“…Epidemiologic evidence suggests an association between PM 10 and PM 2.5 exposure during pregnancy and adverse birth outcomes, including increased infant mortality, LBW, IUGR, and preterm birth (Bell et al, 2010b; Rossner et al, 2011; Rudra et al, 2011). Similar studies have demonstrated no association between fetal air pollution exposure and LBW, suggesting that the correlation between exposure and effect is delicate and might be enhanced by external factors such as region, SES, and duration of exposure (Rossner et al, 2011). A growing body of literature investigating the link between PM exposure and adverse perinatal outcomes has emerged due to the increasing potential of exposure to PM during pregnancy.…”
Section: Adverse Birth Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Toxic chemicals could disturb foetal and placental cellular regulation via elevated DNA adducts and DNA damage [42]. Oxidative damage to placental DNA and increased levels of 8-oxodG in placental DNA can result in intrauterine growth restriction and low birthweight [43]. Maternal tobacco smoke exposure at an epigenome-wide level is associated with placental gene expression and DNA differential methylation and smoking-mediated birthweight reduction [44].…”
Section: Discussionmentioning
confidence: 99%
“…Ambient air exposure to PAHs poses a health risk due to their mutagenic, genotoxic and carcinogenic activity, which was detected only during the last two decades. PAHs are metabolized to form a wide range of products including highly reactive epoxides, which have capacity to bind to DNA, forming PAH-DNA adducts (4,5) and induce oxidative damage (6). Using acellular system Binkova et al (7) observed, that the genotoxicity of respirable particulate matter was related to the content of PAHs.…”
Section: Introductionmentioning
confidence: 99%